Individuals practicing meditation have enhanced subcortical auditory processing of speech. (2nd January 2022) - Sinha, Sujeet Kumar; Sahu, Manisha
Abstract: Background: Meditation is a compound mental task that leads to several changes, both physiologically and psychologically. These physiological changes can occur in the auditory system as well, and this can change the way the stimulus gets coded in the auditory system at both the brainstem as well as cortical level. The present study aimed to investigate the encoding of speech at the brainstem in the individuals who practice meditation. Method: Two groups of 10 male individuals participated in the study. The first group included ten individuals who practiced meditation for a minimum period of 6 months, and the other group consisted of 10 age-matched individuals who never practiced meditation. Speech evoked ABR was recorded for the right ears for all the individuals. FFT analysis of the waveforms was done, and the latency of wave V and amplitude of F0, F1, and F2 were noted. Results: Results of the present study revealed a significantly higher amplitude of F1 and F2 individuals who practiced meditation. However, there was no such significant difference in the latency of wave V and amplitude of F0. Conclusion: The present study reveals that meditation can alter the functioning of the encoding of speech sounds in individuals who practice meditation.